Association between enlarged perivascular spaces and cerebrospinal fluid aquaporin-4 and tau levels: report from a memory clinic - Sacchi, Luca; Arcaro, Marina; Carandini, Tiziana; Pietroboni, Anna Margherita; Fumagalli, Giorgio Giulio; Fenoglio, Chiara; Serpente, Maria; Sorrentino, Federica; Visconte, Caterina; Pintus, Manuela; Conte, Giorgio; Contarino, Valeria Elisa; et al. (Frontiers in Aging Neuroscience, 2023)
Background Perivascular spaces (PVS) are fluid-filled compartments that dilate in response to many different conditions. A high burden of enlarged PVS (EPVS) in the centrum semiovale (CSO) has been linked to neurodegeneration. Moreover, an increase in cerebrospinal fluid (CSF) levels of aquaporin-4 (AQP4), a water channel expressed on PVS-bounding astrocytes, has been described in patients with neurodegenerative dementia. Our aim was to investigate the relationship between neurodegenerative diseases and two putative glymphatic system biomarkers: AQP4 and EPVS. Methods We included 70 individuals, 54 patients with neurodegenerative diseases and 16 subjects with non-degenerative conditions. EPVS were visually quantified on MRI-scans applying Paradise’s scale. All subjects underwent lumbar puncture for the measurement of AQP4 levels in the cerebrospinal fluid (CSF). CSF levels of amyloid-β-1-42, phosphorylated and total tau (tTau) were also measured. Linear regression analyses were adjusted for age, sex, education and disease duration, after excluding outliers. Results Cerebrospinal fluid (CSF)-AQP4 levels were independent predictors of total (β = 0.28, standard error [SE] = 0.08, p = 0.001), basal ganglia (β = 0.20, SE = 0.08, p = 0.009) and centrum semiovale EPVS (β = 0.37, SE = 0.12, p = 0.003). tTau levels predicted CSO-EPVS (β = 0.30, SE = 0.15, p = 0.046). Moreover, increased levels of AQP4 were strongly associated with higher levels of tTau in the CSF (β = 0.35, SE = 0.13, p = 0.008). Conclusion We provide evidence that CSO-EPVS and CSF-AQP4 might be clinically meaningful biomarkers of glymphatic dysfunction and associated neurodegeneration.